2014
DOI: 10.5935/0004-2749.20140056
|View full text |Cite
|
Sign up to set email alerts
|

Inner and outer segment junction (IS/OS line) integrity in ocular Behçet's disease

Abstract: Purpose: In this study, we examined the spectral domain optical coherence tomography (OCT) findings of ocular Behçet's disease (OB) in patients with inactive uveitis. Specifically, we analyzed the inner and outer segment junction (IS/OS line) integrity and the effect of disturbed IS/OS line integrity on visual acuity. Methods: Patient files and OCT images of OB patients who had been followed-up between January and June of the year 2013 at the Dicle University Eye Clinic were evaluated retrospectively. Sixty-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…BD vasculitis can affect large and small arterial or venous vessels [8]. BD can lead to very different clinical outcomes, and diagnosis may be difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BD vasculitis can affect large and small arterial or venous vessels [8]. BD can lead to very different clinical outcomes, and diagnosis may be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Coskun et al [19] reported a decrease in choroidal thickness on enhanced SD-OCT in BD patients. BD can affect the nutrient supply to the photoreceptors and cause photoreceptor damage via its effects on the choroidal vessels [819]. In our study, SD-OCT images were obtained for all participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have demonstrated that decreased foveal thickness and disruption of the photoreceptor inner and outer segment junction detected by OCT are associated with poor visual function, indicating irreversible damage to the macula ( 60 ).…”
Section: Ocular Investigations In Behçet's Diseasementioning
confidence: 99%
“…17,19 Limited information is available regarding the characterization of changes in intraretinal layers around the macula in BD during remission and the association of those changes with VA. Only two cross-sectional studies using OCT described the disruption of photoreceptor ellipsoid zone (EZ) in BD during remission phase. 20,21 These studies reported that the disruption of photoreceptors is strongly related to the loss of VA. However, until now, no studies have quantified the changes of intraretinal thicknesses around the macula in BD that may also dramatically impact the VA.…”
mentioning
confidence: 99%